Analyzing the athletics results of the 6th and 10th Pan Arab Games: A historical and analytical study of the Iraqi results - Al-Attwani, Nidhal Hashim Ghafil (SPORT TK-EuroAmerican Journal of Sport Sciences, 2023)
The purpose of this study is to compile, evaluate, and compare Iraq’s athletic performances in the 6th Pan Arab Games of 1985 and the 10th Pan Arab Games of 2004, in order to present it to future generations and document part of our history in this field. The specific objectives of this research are to identify the results of Iraq in athletics in the 6th Pan Arab Games of 1985 and to identify the results of Iraq in athletics in the 10th Pan Arab Games of 2004. Finally, the results of these two events will be compared and discussed.